Empowering individuals to integrate work and life: insights for management development. Issue 3 (13th April 2015) - Friedman, Stewart D; Westring, Alyssa
Abstract : Purpose: – In efforts to improve employee recruitment and retention and enhance productivity and morale, organizations have implemented policies and practices (e.g. flextime, telework to address employee work-life concerns). However, there is mixed evidence regarding their effectiveness. The purpose of this paper is to complement work-life policies, initiatives aimed at empowering employees with the knowledge and skills to manage multiple life roles may be valuable. Little information is available regarding the nature or effectiveness of such initiatives. Through an in-depth analysis of one initiative, Total Leadership, the authors provide insights that can be used in the selection, design, implementation, and evaluation of work-life empowerment efforts. Design/methodology/approach: – The authors use a mixed methods approach to explore the experiences of 316 participants in the Total Leadership program. Self-assessments (pre and post) were analyzed using quantitative methods (e.g. Cohen's d -value). Inductive and iterative qualitative methods were employed to understand the types of experiments participants created as part of the program. Findings: – The authors found that participants reported significant increases in satisfaction and performance in all domains of life (work, home, community, and self). Further, the authors identified nine types of experiments that individuals used to enhance performance in all life domains. Implications for management development specialists are provided. Originality/value: – This study provides unique and valuable insight for those interested in supporting employee work-life development, leadership, and performance in all domains of life. It represents one of the first efforts to provide evidence-based guidance for the design and implementation of such initiatives.